Microstructure Evolution and Biodegradation Behavior of Laser Rapid Solidified Mg–Al–Zn Alloy - Chongxian He; Shizhen Bin; Ping Wu; Chengde Gao; Pei Feng; Youwen Yang; Long Liu; Yuanzhuo Zhou; Mingchun Zhao; Sheng Yang; Cijun Shuai (Metals, 2017)
The too fast degradation of magnesium (Mg) alloys is a major impediment hindering their orthopedic application, despite their superior mechanical properties and favorable biocompatibility. In this study, the degradation resistance of AZ61 (Al 6 wt. %, Zn 1 wt. %, remaining Mg) was enhanced by rapid solidification via selective laser melting (SLM). The results indicated that an increase of the laser power was beneficial for enhancing degradation resistance and microhardness due to the increase of relative density and formation of uniformed equiaxed grains. However, too high a laser power led to the increase of mass loss and decrease of microhardness due to coarsened equiaxed grains and a reduced solid solution of Al in the Mg matrix. In addition, immersion tests showed that the apatite increased with the increase of immersion time, which indicated that SLMed AZ61 possessed good bioactivity.